RISK AS A REGULATORY TOOL - Rui Vilar; Rui Loureiro (Formifarma, LDA., 2013)
The development of regulations and its application by regulators is moving from a prescriptive approach to a more risk-based one. This work looked at how risk has been used in regulation and how effective has it been its application, in other words how valid is the use of risk as a regulatory tool. A search was made on if and how regulators of different areas have been using risk management. Afterwards a set of public information from a regulator was analysed to find how such an analysis could contribute to a risk-based approach to regulatory action. Findings have shown that although in different stages, tendency in different fields is to increase the use ok risk as a regulatory tool to improve regulatory effectiveness.